Are Retirees More Satisfied? Anticipation and Adaptation Effects: A Causal Panel Analysis of German Statutory Insured and Civil Service Pensioners - Joachim Merz (Institute of Labor Economics (IZA), 2022)
This study contributes to the subjective well-being and retirement literature by quantifying life satisfaction before (4) and after retirement (9+) periods asking: Are retirees more satisfied? Fixed-effects and causal instrumental variables (IV) estimates with individual longitudinal data of the Socio-Economic Panel (SOEP, 33 waves) analyze anticipation and adaptation retirement effects of statutory insured and civil service pensioners in Germany. Main findings: The occupational situation absorbs a positive personal and family influence. There are positive anticipation effects before retirement followed by adaptation instantly when retired both for statutory insured and civil service pensioners. With neutral respectively negative post-retirement adaptation there is no positive retirement effect for both pensioner groups. In short: retirees are not more satisfied, a remarkable result both for statutory insured and civil service pensioners.
Keywords: I31; J26; C21; C23; 330; retirement; statutory insured and civil service pensioners; life satisfaction/subjective well-being; anticipation and adaptation effects; robust fixed-effect regression; causality IV estimates; Socio-Economic Panel (SOEP); Germany